The incidence rate of hepatosteatose in virus carriers with inactive Hepatitis B - Demircan, Fatih; Gozel, Nevzat; Denk, Affan; Kilinc, Faruk (Science & Innovation, Ltd, 2014)
Objective - The aim of this study is to examine the data retrospectively from patients with inactive HBV whose livers were evaluated by ultrasonography and to investigate hepatosteatosis as well as related parameters in this patient group. Material and Methods - In our study, the data of 134 patients, who have applied to the Internal Disease Polyclinic of Elazig cagn Private Medical Center between January 2010 and August 2013 being diagnosed as carriers for inactive HBV and then performed abdominal ultrasonography, were evaluated retrospectively. Information for each patient was accessed by means of both the internal disease polyclinic in our hospital and patient epicrisis reports. The observed levels of plasma trigliserides, LDL cholesterol, AST, ALT, GGT, and ALP were all recorded. Findings - Out of 134 subjects, 72 were male while 62 were female accounting for 54% and 46%, respectively. The mean age of the patients were found to be 44.8 +/- 10.6 years old. Hepatosteatosis was found in 92 patients accounting for 68.7 %. The mean of age in some patients diagnosed with steatosis was found 50.1 +/- 7.6 years, while the others without steatosis was 33.2 +/- 6.0 years suggesting a significant difference compared to the former (p = 0.001). Furthermore, a consistency in difference was also found between these two groups with and without hepatosteatosis in terms of average triglyceride levels (p = 0.001). The mean GGT levels were consistently higher in the group with hepotosteatosis (p = 0.004). No significant difference was found between these two groups regarding their mean cholesterol levels of AST, ALT, ALP, and LDL. Conclusion - In patients with asymptomatically HBV infection, an increased risk for hepatosteatosis comes along with an increased levels of plasma triglycerides and GGT in the course of aging.
Keywords: inactive HBV carriers; hepatosteatosis; ultrasonography